Extended familial risk of suicide death is associated with younger age at death and elevated polygenic risk of suicide. Issue 3 (24th February 2022) - Coon, Hilary; Shabalin, Andrey; Bakian, Amanda V.; DiBlasi, Emily; Monson, Eric T.; Kirby, Anne; Chen, Danli; Fraser, Alison; Yu, Zhe; Staley, Michael; Callor, William Brandon; Christensen, Erik D.; et al.
Abstract: Suicide accounts for >800, 000 deaths annually worldwide; prevention is an urgent public health issue. Identification of risk factors remains challenging due to complexity and heterogeneity. The study of suicide deaths with increased extended familial risk provides an avenue to reduce etiological heterogeneity and explore traits associated with increased genetic liability. Using extensive genealogical records, we identified high‐risk families where distant relatedness of suicides implicates genetic risk. We compared phenotypic and polygenic risk score (PRS) data between suicides in high‐risk extended families (high familial risk (HFR), n  = 1, 634), suicides linked to genealogical data not in any high‐risk families (low familial risk (LFR), n  = 147), and suicides not linked to genealogical data with unknown familial risk (UFR, n  = 1, 865). HFR suicides were associated with lower age at death (mean = 39.34 years), more suicide attempts, and more PTSD and trauma diagnoses. For PRS tests, we included only suicides with >90% European ancestry and adjusted for residual ancestry effects. HFR suicides showed markedly higher PRS of suicide death (calculated using cross‐validation), supporting specific elevation of genetic risk of suicide in this subgroup, and also showed increased PRS of PTSD, suicide attempt, and risk taking. LFR suicides were substantially older at death (mean = 49.10 years), had fewer psychiatric diagnoses of depression and pain, and significantly lower PRS of depression. Results suggest extended familiality and trauma/PTSD may provide specificity in identifying individuals at genetic risk for suicide death, especially among younger ages, and that LFR of suicide warrants further study regarding the contribution of demographic and medical risks.